INTERACTIVE TECHNIQUES IN TEACHING LISTENING TO B2 LEVELS - Abdurakhmonova Iroda Xolbozor qizi (Ta'lim innovatsiyasi va integratsiyasi, 2025)
Abstract:Listening comprehension is a fundamental skill for language learners, especially at the B2 level, where they are required to understand complex and fast-paced spoken discourse. This paper explores interactive techniques that can enhance students' listening skills by making lessons more engaging, dynamic, and effective. The study highlights pre-listening, while-listening, and post-listening activities, as well as the role of technology in improving listening proficiency. Listening  is  one  of  the  essential  components  of  language  learning,  enabling learners to grasp meaning from spoken texts, engage in conversations, and enhance their  overall  communication  skills.  However,  many  students  at  the  B2  level  face difficulties in understanding authentic audio materials due to speed, accent variations, and complex vocabulary. To address these challenges, interactive teaching techniques play a crucial role in developing effective listening strategies.